Pemberdayaan Kader Posyandu Balita melalui Program Pelatihan Deteksi Dini Pertumbuhan dan Perkembangan pada Balita di Desa Panaikang - Indra Dewi; Susi Sastika Sumi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Children under five years of age or often abbreviated as toddlers are children who have reached the age of over one year or calculated by the age of 12-59 months. Experts have classified toddlers as a stage of child development that is very vulnerable to disease attacks or lack or excess nutritional intake. One optimal way to support children's growth and development is by monitoring growth and development at the posyandu. The readiness of posyandu cadres is one of the posyandu services in providing basic services. Activities to monitor children's nutritional status are supported by the community who come to the posyandu through cadre participation. The aim of this community service is to provide training to cadres about Panaikan Village. The target of this community service is posyandu cadres. Community service is carried out for 2 days. The methods used are pretest, education, training and posttest. The Pre Test was carried out to determine the cadres' initial knowledge about early detection of growth and development in toddlers. Then education and training was carried out regarding early detection of growth and development in toddlers. After that, a Post Test was carried out. The post test was carried out to determine the results of cadre training regarding early detection of growth and development in toddlers.